CSFs for Six Sigma in service and manufacturing companies: an insight on literature. Issue 4 (8th October 2018) - Pathiratne, Sonali Udeeka; Khatibi, Ali; Md Johar, Md Gapar
Abstract : Purpose: This paper aims to identify and review the critical success factors (CSFs) for successful Six Sigma implementation in service and manufacturing companies given in published literature. Design/methodology/approach: A descriptive evaluation of the literature body is followed by future research opportunities. Studies published on the topic of Six Sigma during 2005-2016 are reviewed to retrieve identified CSFs. Findings: From published literature, 48 CSFs vital for Six Sigma implementation were identified. The identified CSFs were classified under eight core categories. As per the categorization, 35 out of 48 CSFs identified are either Company Strategy related, Six Sigma Project related or Human Resources related. Only a limited number of studies are carried out mainly focusing on the stated three core areas. Hence, it is vital that these three core areas are further explored in future research. Originality/value: With the outcome of this paper, the identified CSFs for Six Sigma will be taken for further studies, where they will be applied to service and manufacturing companies based in Sri Lanka. Hence, it would provide Sri Lankan service and manufacturing companies guidelines for successful implementation of Six Sigma for future endeavors.